2004
DOI: 10.1086/420822
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Specific Risk Factors and Protective Factors for Acute Diarrheal Illness in Children Aged 12-59 Months in Sao Paulo, Brazil

Abstract: Diarrheal diseases are a leading cause of childhood morbidity and mortality in Latin America. Most studies have focused on infants but not on older children. We enrolled 505 children (age, 12-59 months) with diarrhea and age-matched controls in a case-control study in Sao Paulo, Brazil. Independent risk factors for diarrhea included another household member with diarrhea (matched odds ratio [mOR], 8.1; attributable fraction [AF], 0.17; P<.001) and consumption of homemade juice (mOR, 1.8; AF, 0.10; P=.01); prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 24 publications
(22 reference statements)
3
44
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
“…In Cochabamba, Bolivia, the site of this study, the most recent government survey from 2008 reported a diarrhea prevalence of 36.2% for children 5 years of age for the department. 2 Previous studies have identified risk factors for diarrhea such as younger age, 3,4 male gender, 4,5 early weaning, 5-8 seasonal patterns, 5,7,9 low maternal education, 5,9,10 lack of piped water supply, 9,[11][12][13][14][15] poor water-storage practices, 9,14-18 younger maternal age, 11,12 lack of hand washing with soap by caregiver, 18,19 poor sanitation, 9,16,18,20,21 visible feces in the yard, 4 indiscriminate disposal of child feces, 17 unsatisfactory garbage disposal, 11 shorter boiling time, 13 using water from cistern trucks, 13 and not treating water in the home. 13 In a recent multisite study it was found that rotavirus was the most common cause of moderate to severe diarrhea in children 0-23 months of age, and shigellosis for the age group 24-59 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies have identified lack of caregiver handwashing with soap and drinking water treatment, poor water storage practices, and lack of caregiver knowledge of diarrhea prevention as important risk factors for diarrheal disease in pediatric populations. [2][3][4][5][6][7][8] Water, sanitation, and hygiene (WASH) interventions promoting household chlorination of drinking water and handwashing with soap have the potential to reduce diarrheal disease incidence in children less than 5 years of age by an estimated rate of 20-40%. [9][10][11] However, in many low-income countries, community-based WASH interventions are often difficult to implement in urban settings because of limited community health work infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, single pathogens were isolated in the group aged two years and younger. Previous studies have shown that children living in impoverished areas are colonized soon after weaning and are probably re-infected during the rest of their childhood [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhoeal diseases constitute a major worldwide public health problem, especially in poor or developing countries [1]. The World Health Organization (WHO) has estimated that annually 4.6 to 5 million children under five years of age die of diarrhoea in Asia, Africa, and Latin America [2].…”
Section: Introductionmentioning
confidence: 99%